The oncogenic role of Epstein–Barr virus‐encoded microRNAs in Epstein–Barr virus‐associated gastric carcinoma. Issue 1 (9th October 2017) - Zhang, Jinglin; Huang, Tingting; Zhou, Yuhang; Cheng, Alfred S. L.; Yu, Jun; To, Ka Fai; Kang, Wei
Abstract: Epstein–Barr virus (EBV) infection is detected in various epithelial malignancies, such as nasopharyngeal carcinoma (NPC) and gastric cancer (GC). EBV comprises some unique molecular features and encodes viral genes and microRNAs (miRNAs) by its own DNA sequence. EBV genes are required to maintain latency and contribute to oncogenic property. miRNAs encoded by EBV have been shown to contribute to initiation and progression of EBV‐related malignancies. By a number of genomic profiling studies, some EBV miRNAs were confirmed to be highly expressed in EBV‐associated gastric cancer (EBVaGC) samples and cell lines. The majority host targets of the EBV miRNAs are important for promoting cell growth and inhibiting apoptosis, facilitating cell survival and immune evasion. However, the integrated molecular mechanisms related to EBV miRNAs remain to be investigated. In this review, we summarized the crucial role of EBV miRNAs in epithelial malignancies, especially in EBVaGC. Collectively, EBV miRNAs play a significant role in the viral and host gene regulation network. Understanding the comprehensive potential targets and relevant functions of EBV miRNAs in gastric carcinogenesis might provide better clinical translation.